Effect of Introduction of Lu on Thermal Stability and Luminescence Properties of YAG:Ce3+, Sm3+ Using Orthogonal Experiments. Issue 1 (2nd January 2021) - Li, Guozhen; Lu, Liping; Sun, Haiying
ABSTRACT: Y(Lu)AG:Ce 3+, Sm 3+ yellow phosphors were prepared by molten salt method with 0.1NaCl-0.1KCl-0.8NaF as the molten salt. The effects of multi-factor variables on the properties of Y(Lu)AG:Ce 3+, Sm 3+ phosphors were comprehensively studied by orthogonal experiments which is a method to study the experiment with multi-factor variables and select some representative ones from the comprehensive experiment to find the optimal experimental conditions. The optimum synthesis conditions were as follows: Ce 3+ concentration 0.06 mol%, Lu 3+ concentration 0.5 mol%, Sm 3+ concentration 0.02 mol%, calcination temperature 1300 o C, insulation time 1.5 h. The effects of introduction of Lu 3+ on the crystal structure, temperature stability and luminescence properties of YAG:Ce 3+, Sm 3+ were studied. The results showed that due to the introduction of Lu 3+ ions, the matrix lattice slightly changed (belonging to the cubic crystal system), the emission peak was blue shifted, temperature stability improved and decay reduced, which plays an important role in improving the lifetime of white LEDs. GRAPHICAL ABSTRACT: